Spatio-temporal mechanisms of consolidation, recall and reconsolidation in reward-related memory trace - Hamed, Adam; Kursa, Miron Bartosz; Mrozek, Wiktoria; Piwoński, Krzysztof Piotr; Falińska, Monika; Danielewski, Konrad; Rejmak, Emilia; Włodkowska, Urszula; Kubik, Stepan; Czajkowski, Rafał (Molecular psychiatry, 2025)
The formation of memories is a complex, multi-scale phenomenon, especially when it involves integration of information from various brain systems. We have investigated the differences between a novel and consolidated association of spatial cues and amphetamine administration, using an in situ hybridisation method to track the short-term dynamics during the recall testing. We have found that remote recall group involves smaller, but more consolidated groups of neurons, which is consistent with their specialisation. By employing machine learning analysis, we have shown this pattern is especially pronounced in the VTA; furthermore, we also uncovered significant activity patterns in retrosplenial and prefrontal cortices, as well as in the DG and CA3 subfields of the hippocampus. The behavioural propensity towards the associated localisation appears to be driven by the nucleus accumbens, however, further modulated by a trio of the amygdala, VTA and hippocampus, as the trained association is confronted with test experience. Moreover, chemogenetic analysis revealed central amygdala as critical for linking appetitive emotional states with spatial contexts. These results show that memory mechanisms must be modelled considering individual differences in motivation, as well as covering dynamics of the process.
Keywords: Animals; tegmentum mesencephali - area ventralis; hipokampus; Cues; rozpomínání; strojové učení; Nucleus Accumbens; amfetamin; Mental Recall; Memory; neurony; mozek; Memory Consolidation; Reward; prefrontální mozková kůra; Ventral Tegmental Area; Neurons; podněty; Male; amygdala; Brain; Machine Learning; nucleus accumbens; Amygdala; Amphetamine; konsolidace paměti; krysa rodu Rattus; paměť; Hippocampus; mužské pohlaví; zvířata; odměna; Rats; Prefrontal Cortex